THERAPEUTIC MANAGEMENT OF RUMINAL ACIDOSIS IN GOATS - Ram, Pradeep Kumar; Verma, Subhash Prasad; Agrawal, Anup Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The present investigation was undertaken with a view to observe changes in clinical signs and symptoms in goats suffering from different degrees of rumen acidosis (mild , moderate and severe) and their response to different therapeutic approaches. The study was conducted in 27 clinical cases of acidotic goats and compared with 6 healthy control goats. Mild acidotic goats got only oral therapy of a combination of Anigest powder, Rumbion bolus, Soda bi-carb and Ambiplex syrup, moderate acidotic goats were treated with the above combination along with parenteral administration of Soda bi-carb, Anistamin and Dexona, whereas severe acidotic goats were given Steclin bolus, Yea-Sacc bolus, ruminal cud and normal saline in addition to the above therapeutic measures. Two out of five goats of severe acidotic group died on 3rd day during treatment whereas rest 25 goats responded well to the therapeutic measures and recovered. Various drugs are having their particular properties, which are used for treating this disease in field conditions.
Keywords: acidosis; goats; symptoms; treatment